TINJAUAN HUKUM HAK CIPTA TERHADAP TINDAKAN PENJUALAN AKUN NETFLIX TIDAK RESMI DALAM MEDIA SOSIAL - Tasya Maura Donita; Moch Najib Imanullah (Jurnal Privat Law, 2026)
This articles aims to find out and analyze the copyright protection of netflix paid streaming application programs in the study of trading unofficial netflix accounts on social media. This study uses a combination of normative methods and descriptive empirical methods. This research approach uses a qualitative approach by using primary legal materials and secondary book materials. The technique of collecting legal materials in writing this law uses library research and interview techniques. According to Law of the Republic of Indonesia Number 28 of 2014 on Copyright, the Netflix paid streaming application is a computer program and is included in a protected work. Along with the development of technology and social media, the act of buying and selling netflix accounts unofficially began to bloom on social media. The results of research and studies in writing this law show that Law of the Republic of Indonesia Number 28 of 2014 on Copyright regulates the prohibition of commercializing unofficial netflix accounts on social media. This study aims to increase public awareness of the applicable law and the importance of copyright which requires an active government role in controlling copyright in social media. So it can be concluded that there needs to be an increase in supervision from the Directorate General of Intellectual Property so that the Netflix application can improve the user account security system so that the public is able to respect copyright more.